2007
DOI: 10.1074/jbc.m611004200
|View full text |Cite
|
Sign up to set email alerts
|

The Lipoxin A4 Receptor Is Coupled to SHP-2 Activation

Abstract: Mesangial cell proliferation is pivotal to the pathology of glomerular injury in inflammation. We have previously reported that lipoxins, endogenously produced eicosanoids with anti-inflammatory and pro-resolution bioactions, can inhibit mesangial cell proliferation in response to several agents. This process is associated with elaborate receptor cross-talk involving modification receptor tyrosine kinase phosphorylation (McMahon,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(6 citation statements)
references
References 47 publications
1
5
0
Order By: Relevance
“…Furthermore, we also speculate that this lipid analogue could be able to inhibit SHP-2, because, as reported previously, LXs inhibit mesangial cell proliferation via SHP-2 inhibition (Wu et al, 2005). In addition, it has been shown that ALX is coupled to activation and recruitment of SHP-2 (Mitchell et al, 2007). Further experiments are required to confirm this hypothesis and whether other phosphatases could be involved, such as PTEN (phosphatase and tensin homologue), as this phosphatase can negatively modulate VEGF-induced angiogenic effects, including cell survival, proliferation and migration (Huang and Kontos, 2002).…”
Section: Atl-1 Inhibits Multiple Steps Of Angiogenesissupporting
confidence: 75%
“…Furthermore, we also speculate that this lipid analogue could be able to inhibit SHP-2, because, as reported previously, LXs inhibit mesangial cell proliferation via SHP-2 inhibition (Wu et al, 2005). In addition, it has been shown that ALX is coupled to activation and recruitment of SHP-2 (Mitchell et al, 2007). Further experiments are required to confirm this hypothesis and whether other phosphatases could be involved, such as PTEN (phosphatase and tensin homologue), as this phosphatase can negatively modulate VEGF-induced angiogenic effects, including cell survival, proliferation and migration (Huang and Kontos, 2002).…”
Section: Atl-1 Inhibits Multiple Steps Of Angiogenesissupporting
confidence: 75%
“…The in vivo agonist and anti-inflammatory and pro-resolving actions of this eicosanoid and related compounds have now been independently confirmed and extended by many investigators worldwide [3, for recent reviews, see refs. 33, 34, and 35, 36, 37]. …”
Section: Pro-resolving Gpcrsmentioning
confidence: 99%
“…We suggest that good candidate molecules for this AE-derived suppressive effect are the family of resolving mediators of inflammation which include the lipoxins, resolvins and protectins [23]. Several lines of evidence support involvement of this class of mediators: i) they have already been shown to be important in epithelial cell function and repair [24] and to have a potential role in airway hyperresponsiveness [25−27] and asthma [28]; ii) they work through G 0 /Gi protein coupled receptors [29]; iii) their synthesis often requires a contribution from AEC [30]; iv) we have demonstrated for the first time that lipoxin A4, resolvin D 1 and resolvin D 2 , are potent inhibitors of HLMC degranulation and v) biochemical fractionation indicates that the activity in AEC supernatant is a <10 kDa lipid which would fit the profile of a resolving mediator.…”
Section: Discussionmentioning
confidence: 98%